(untitled) (Revista Brasileira de Contabilidade e Gestão, 2017)
The organizations providing financial services have been important allies of small and medium enterprises, however needs present updated solutions to its clients not to become obsolete. The use of Business Process Outsourcing accounting and tax is demanded from companies as a strategic solution and can then release more time and efforts on their core business. This paper analyzed the characteristics of BPO in midsize companies in Caxias do Sul, being held for this purpose a literature search to identify the characteristics of BPO, followed by desk research to identify the hours and amounts paid to the office by accounting fees. Finally entrepreneurs were interviewed to identify their perception about BPO characteristics. It was concluded that the use of tax and accounting BPO reduced costs in four of the five companies studied. Yet the scale of costs is no unanimity on this when companies opt for outsourcing niche, considering the knowledge of professionals, management of the activity and gains in operational efficiency of paramount importance for the results and the satisfaction of the entrepreneur.